APPLICATION OF COGNITIVE CONFLICT LEARNING STRATEGIES TO REDUCE MISCONCEPTION ON HIGH SCHOOL STUDENTS - AHMAD HANAFI, JOE; ARIFIN IMAM SUPARDI, ZAINUL (Inovasi Pendidikan Fisika, 2019)
The purpose of this study is to find out student?s conception profile after cognitive conflict teaching strategy has been applied through learning model guided inquiry. Pre-test showed that misconception level of student in a high level, that is 61,02%. The effort to reduce student?s misconception is by given cognitive conflict strategy to the student?s with expectation that student will be aware of their wrong conception so that they decided to change their wrong conception. Conflict Cognitive is given through learning model guided inquiry. CRI (certainty of response index) is used to identify student?s conception. Conflict cognitive strategy can reduce the level of student?s misconception according to the outcome. Post-test result showed that misconception percentage is downgrade to 20,00%.Key Word: Misconception, Cognitive Conflict, CRI